Keterkaitan Kota Demak terhadap Kota Semarang dalam Lingkup Wilayah Metropolitan - Triani Agustina Rahayu (Department of Urban and Regional Planning, Diponegoro University, 2013)
The use of space for the population at large concentration of activities located at large cities such as metropolitan regions. The process of urbanization that occurred in those cities takes place dynamically and even showed an increasing trend. Metropolitan regions consists of at least one main city and several satellite city in it. Incorporated cities within the metropolitan region tend to interact among each other, especially between the satellite city with its main city. The interaction between the satellite cities and main city is very interesting to study more deeply that it was appointed as the topic of this research. Demak city as one of the satellite city in the Province of Central Java has a relationship with a city that has a higher hierarchy, Semarang City. The appeal of the main city cause the population more interested in physical activities at Semarang City than at Demak City. By using quantitative approaches and techniques of quantitative analysis descriptive statistics and cross tabulation analysis, this study aims to determine the form of interaction on the Demak City to Semarang City. Based on these results, the form of physical interaction of the city of Demak to Semarang establish a dependency, because the existence of Semarang influence in the field of transport, given the two cities are connected by a path which is the main route for Central Java Regional movement so if the physical condition of the City Semarang is not possible to go through then it can not happen the movement from Demak. Forms of economic interaction of the city is a dependency, because it occurs only in one direction from Demak especially at urban facilities, movement residents of Demak City to Semarang city to access the urban facilities that are not available in Demak, so in the field of urban facilities Demak City still depends on Semarang City. Forms of social interaction from the city of Semarang Demak against linkage, namely the relationship which is independent, the population affects the population in the city of Semarang Demak in the occurrence of social linkages.